2023
DOI: 10.1093/haschl/qxad005
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of private payers on multicancer early-detection tests: informing research, implementation, and policy

Abstract: Emerging blood-based multicancer early-detection (MCED) tests may redefine cancer screening, reduce mortality, and address health disparities if their benefit is demonstrated. U.S. payers’ coverage policies will impact MCED test adoption and access; thus, their perspectives must be understood. We examined views, coverage barriers, and evidentiary needs for MCED from 19 private payers collectively covering 150 000 000 enrollees. Most saw an MCED test's potential merit for cancers without current screening (84%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…Findings from the current study suggest that when patients are provided information about MCED testing that focuses on the describing the logistics of having a "simple" blood test for cancer screening, patient interest in having MCED testing is likely to be very high. Before making MCED testing widely available to primary care patients, however, health systems and health care providers should consider not only the results of clinical trials, but also how to address the need to provide patients with more complete information about the pros and cons of MCED testing, including details related to test use in concert with other types of recommended cancer screening tests, procedures required for following up abnormal MCED test findings, and insurance coverage and costs associated with testing and follow-up [29]. Attention should also be paid to addressing provider concerns related to the time required for patient education and decision support, along with the management of false positive and false negative findings.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the current study suggest that when patients are provided information about MCED testing that focuses on the describing the logistics of having a "simple" blood test for cancer screening, patient interest in having MCED testing is likely to be very high. Before making MCED testing widely available to primary care patients, however, health systems and health care providers should consider not only the results of clinical trials, but also how to address the need to provide patients with more complete information about the pros and cons of MCED testing, including details related to test use in concert with other types of recommended cancer screening tests, procedures required for following up abnormal MCED test findings, and insurance coverage and costs associated with testing and follow-up [29]. Attention should also be paid to addressing provider concerns related to the time required for patient education and decision support, along with the management of false positive and false negative findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some health plans provide MCD tests as part of their screening programs; however, in a recent study of 19 major private payers, none reported covering MCD testing. 7 The usefulness of a cancer screening test to reduce cancer morbidity and mortality is interrelated with test performance measures, such as sensitivity (correctly detecting a cancer signal in those with cancer) and specificity (correctly identifying a cancer signal only in those with cancer), the acceptability and affordability of the test, the potential burden and costs of the diagnostic workup after a positive MCD screening result, and effective cancer care delivery that leads to improved patient outcomes, including survival. To date, cancer detection tests recommended for widespread population screening (breast, cervix, colon, and lung) have demonstrated improvements in cancer-specific mortality.…”
Section: Introductionmentioning
confidence: 99%
“…At this time, no MCD tests have received marketing authorization by the US Food and Drug Administration (FDA). Some health plans provide MCD tests as part of their screening programs; however, in a recent study of 19 major private payers, none reported covering MCD testing 7 …”
Section: Introductionmentioning
confidence: 99%